The Layout of the Combustion Cavity and the Fracture Evolution of the Overlying Rock during the Process of Underground Coal Gasification. (4th April 2022) - Li, Zhaolin; Wang, Lianguo; Ren, Bo; Ding, Ke
Abstract : Based on the thermodynamic and elastodynamic theories, the controlling equation of temperature-stress coupling action on rocks containing random damage units is established by combining the Mogi-Coulomb damage criterion. And the numerical calculation model of combustion cavity expansion under temperature-stress coupling condition is established by using ABAQUS secondary development program. The fracture field evolution law during the expansion of the gasification cavity was studied under two conditions: perpendicular to (condition 1) and along the intermediate principal stress (condition 2). It is found that under the condition 1, the gasification cavity gradually forms a smaller fracture circle, while the surrounding rock at the floor of the gasification cavity generates a wide range of equivalent damage areas under the condition 2, which is unfavorable for practical engineering. The condition 1 deployment scheme is more practical in terms of the degree of rupture and the subsequent gasification process. The gasification cavity is obviously affected by the horizontal stress. When the horizontal stress is small, the stability of the surrounding rock is seriously damaged. It is necessary to fully consider the influence of in situ stress in the layout of the gasification cavity; at the same time, measures are added to the process to reduce the degree of rupture of the surrounding rock. The evolution law of the temperature field and rupture field of the surrounding pressure in the combustion cavity during the whole process of UCG was numerically simulated. The floor rupture zone develops gradually with the advancement of the working face of the combustion cavity, and deeper rupture zones appear in several areas, which need special attention in the engineering.